Secular Trends in Pubertal Timing among Ambonese Adolescents: A Comparative Analysis - Ayu, Rizki (Scientific Journal of Pediatrics, 2023)
Introduction: The timing of puberty is a crucial developmental milestone with significant implications for adolescent physical and psychosocial health. While secular trends towards earlier pubertal onset have been observed in many populations worldwide, data from Ambonese adolescents in Indonesia remains limited. This study aimed to investigate secular trends in pubertal timing among Ambonese adolescents and explore potential influencing factors. Methods: A retrospective cross-sectional study was conducted involving Ambonese adolescents aged 10-18 years who attended health clinics in Ambon City between 2008 and 2023. Data on age at menarche for girls and testicular volume for boys, along with socioeconomic and lifestyle factors, were collected from medical records. Age at menarche and testicular volume were used as markers of pubertal onset. Statistical analyses were performed to assess trends over time and identify associations with potential influencing factors. Results: A total of 1,542 adolescents (785 girls and 757 boys) were included in the study. The mean age at menarche decreased significantly from 12.8 years in 2008 to 12.3 years in 2023 (p < 0.001). Similarly, the mean testicular volume at age 14 increased significantly from 12.5 ml in 2008 to 14.2 ml in 2023 (p < 0.001), suggesting earlier pubertal onset in boys. Improved socioeconomic status and increased body mass index (BMI) were associated with earlier pubertal onset in both sexes. Conclusion: This study provides evidence of a secular trend towards earlier pubertal onset among Ambonese adolescents. Socioeconomic factors and BMI appear to play a role in influencing pubertal timing. Further research is needed to explore the underlying mechanisms and potential health implications of these trends.